Molecular Identification of Encephalartos (Zamiaceae) Species and Their Relationships to Morphological Characters - Chaiprasongsuk, Minta; Mingmuang, Mingkwan; Thongpan, Amara; Namwongprom, Kamolpun (Agriculture and Natural Resources, 2007)
RAPD and morphological characteristics were used to evaluate genetic similarity among twenty species of Encephalartos geographically distributed in several African countries. Eight out of sixty primers, i.e. OPA-05, OPA-07, OPB-07, OPB-08, OPB-11, OPJ-07, OPJ-13, and OPJ-15 could produce polymorphic and specific band patterns to identify these cycads. The primers generated 240 reproducible bands at the size of 0.15 - 2.20 kb. Polymorphism of the DNA profiles appraised by NTSYS program gave the similarity coefficient in the range of 0.53-0.80. Phylogenetic tree was constructed and twenty Encephalartos species were grouped into six clusters. The grouping corresponded well to the nine morphological characters (stem, color of rachis, leaf curvation, spiny leaflet, number of prickle, leaflet shape, keel, upper and lower margins of leaflet) as well as to their original geographic distribution.